Improving the structural behaviour RC precast concrete beams made of recycled aggregate concrete - Lapko, Andrzej; Grygo, Robert (Journal of Civil Engineering and Management, 2016)
The application of concrete waste for recycled aggregate concrete (RAC) used in structural members is associated with an increased risk for the structure due to, e.g. pollutions in the old crushed concrete and random variable strength. A new concept of RC flexural members like beams and slabs made of RAC with strengthening inclusion was elaborated and presented in the paper based on application of precast concrete inserts made of HSC, located in the compression zone of the members. The paper presents the results of experimental and numerical (FEM) analysis carried out on such composite beams. The results of experimental research on the behavior of such beams and numerical simulations using Diana computer program reveal some positive effects, such as higher stiffness and flexural capacity of the innovative beams compared to the reference beams made fully of RAC.